DOP005 Safety of vedolizumab in patients naïve to treatment with TNF antagonists compared with patients with prior use of TNF antagonists. (16th January 2018) - Cohen, R; Bhayat, F; Hantsbarger, G; Blake, A; Vermeire, S
Abstract: Background: Vedolizumab is a gut-selective antibody approved for the treatment of adults with moderate to severe ulcerative colitis (UC) and Crohn's disease (CD). Data from the GEMINI open-label extension (OLE) study and the post-marketing (PM) setting were analysed to investigate whether the safety of vedolizumab differed between patients naïve to treatment with tumour necrosis factor (TNF) antagonists and those who had previously used TNF antagonists. Methods: Adverse events (AEs) from the OLE and the PM Global Safety Database (cut-off: 19 May 2017) were classified by MedDRA Preferred Terms for TNF antagonist-naïve and -experienced patient groups. Exposure adjusted incidence rates were calculated for the OLE patients. Results: In the OLE study, 41.3% of patients were naïve to TNF antagonists (Table 1). These patients experienced significantly fewer AEs (94 vs. 275 per 100 patient years [PYs]) and serious AEs (10 vs. 18 per 100 PYs) than TNF antagonist experienced patients. The following AE groupings had a higher incidence per 100 PYs in TNF antagonist experienced vs. -naïve patients: infections (69 vs. 31), skin and subcutaneous tissue disorders (SSTD; 17 vs. 7) and malignancies (3 vs. 1; Table 2). In the PM setting, 23.7% of patients who reported an AE were TNF antagonist naïve. The most commonly reported AEs in both groups were: increased blood pressure, fatigue, exacerbated UC, headache and arthralgia (Table 3). These AEs, and other clinically relevant AEs, including SSTD, infections and malignancies were reported by a similar proportion of patients in both groups. Most patients continued treatment despite an AE in both settings. Conclusions: In the OLE study, a higher incidence of clinically relevant AEs was observed in TNF antagonist experienced vs. naïve patients. In the PM setting, a similar proportion of patients reported each AE in both groups. Limitations of PM safety reports, including incomplete data, voluntary reporting, increased reporting of more serious events and difficulty establishing a causal relationship between drug and event must be considered when interpreting these results.